Persistence of behavioral abnormalities following corticosteroid therapy in children with initial episode of idiopathic nephrotic syndrome: a prospective longitudinal observation - Parichay Singh; Om P. Mishra; Shashi K. Upadhyay; Rajniti Prasad; Ankur Singh; Abhishek Abhinay; Akash Mishra; Franz Schaefer (Brazilian Journal of Nephrology, 2021)
Abstract Introduction: Treatment of nephrotic syndrome with corticosteroid can cause several side- effects including behavioral abnormalities. The objectives of the study were to observe the proportion of non-relapsers having persistence of behavioral abnormalities after completion of treatment of initial episode and compare the abnormalities with relapsers, and to determine risk factors for persistence. Methods: Seventy-five children with a first episode of idiopathic nephrotic syndrome and 60 normal children were rated by parents for behavioral problems using the Child Behavior Checklist. The Parenting Stress Index was also evaluated. The children were rated before treatment and 12 and 36 weeks after. Results: Both relapsers and non-relapsers showed abnormalities in internalizing and externalizing domains at 12 weeks of steroid therapy. Non-relapsers had abnormal scores in the internalizing domain in 63.5 % and externalizing domain in 48.1% of cases at 36 weeks. Relapsers had abnormal scores in all the three behavior domains, but a significantly higher proportion of relapsers had abnormal scores regarding total behavior (65.2% vs 28.8%, p<0.01) and child domains (100% vs 57.7%, p<0.001) of Parenting Stress Index in comparison to non-relapsers at 36 weeks. Occurrence of relapse increased the risk (odds ratio 5.76, 95% CI 1.35-10.76, p< 0.001) for persistence of abnormal total behavior at 36 weeks follow-up. Conclusion: Persistence of abnormalities was observed not only in relapsers but also in non-relapsers. Relapse was found to be a significant risk factor for persistence of abnormal behaviors in these patients.